Investigating university student engagement in online learning: A case study in EFL classroom - Ignasia Yuyun (Indonesian Journal of Applied Linguistics, 2023)
The COVID-19 pandemic outbreak inevitably impacts the shift in teaching and learning activities worldwide. Online learning has been commonly applied in education, particularly in higher education. Notably, student engagement plays a pivotal role in the online classroom as it identifies critical elements of the learning process that can increase learning and outcomes. However, the question has been raised about whether student engagement between synchronous and asynchronous online classrooms is indistinguishable. Thus, this study investigates student engagement in a synchronous and asynchronous online classroom, particularly in an Indonesian English as a Foreign Language (EFL) context. A Likert-scale questionnaire and classroom observation (synchronous and asynchronous) were used to gather the data from 26 university students in a sample of EFL teaching in an Indonesian context. The study encompasses five elements of online engagement: social engagement, cognitive engagement, behavior engagement, collaborative engagement, and emotional engagement. The prominent finding has successfully revealed that university student engagement in online learning has different significance levels. Most students are more involved in synchronous online activities as they can interact with their professors and peers in real time. Synchronous and asynchronous learning provide substantial and comparable results. This study implies that synchronous and asynchronous activities should be incorporated into online learning to get more engaging interaction among students. This study has contributed to the growing literature on the student-teacher dynamic in online education. Further research could explore student engagement in online learning from other perspectives, such as the teacher's perspective and the use of learning media.